Free Hand Versus Anatomical Patient Suited Operative Techniques For Cup Abduction In Total Hip Surgery: A Comparative Study (Journal of Pharmaceutical Negative Results, 2023)
Background: Replacement arthroplasty of the hip is one of the common operations in orthopedic practice and the final success depends on the stability of the implant which depends largely on the proper orientation of the cup during sugary, free hand technique is the commonest conventional method used in practice for cup inclination. A more anatomical methods are adapted to seat the cup abduction such as the use of acetabular fossa all aiming at a better patient directed stable cup.Aims of the Study: To compare the results of the use of acetabular fossa against the use of free hand technique for preoperative seating of acetabular cup inclination in primary cement less hip replacement by the use of post-operative antero-posterior pelvic X-ray to measure the angle of cup abduction and the clinical subjective result as described by the patient.Method: This is a comparative study which was done during the period from July 2017 to march 2022 in the Medical City directorate, Baghdad - Iraq by one surgical team, All patients treated with the same type of primary cement less replacement of the hip through a Postero-lateral approach during the study period and were divided into two groups; group A of 34 patients where free hand technique used for seating of cup inclination and group B of 36 patients where acetabular fossa used as an anatomical reference for preoperative cup inclination. The results were assessed by the use of antero-posterior pelvic X-ray for measurement of cup abduction and the use of a subjective patient directed clinical outcome for the result of the surgery after two weeks and after three months of operation which was given by the patient as good, fair or bad.Results: The safe zone of abduction angle identified by Lewinnek et al. which is 40°±10° was used as a gold standard for assessment of the cup inclination. The shortest follow up period was three months. All the angles for the 2 groups fell within the safe zone of Lewinnek, 42.03 ± 4.23 for group A and 42.67 ± 3.92 for group B The patient based clinical outcome was assessed according to WOMAC scoring system and regarding pain domain improved from 12.1±0.98, to 3.6±0.8 2 weeks after surgery and 2.9±0.6 3 months postoperatively and physical activity improved from 43.2±8.1 preoperatively to 26.7±2.2 two weeks after surgery and18.4±1.6 3 months postoperatively for group A with statistically significant result P value <0.05.Conclusion: A proper preoperative planning and templating as well as a standardized patient set up are of prime importance in proper cup placement regardless the operative technique used.